UMAR IBN KHATAB EXPANSI DAN REALISASI PENCAPAIAN - Umi Fitri Lestari; Afrizal; Syawaluddin; Wiji Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Umar Ibn Khattab was one of the most influential caliphs in Islam. Significant expansion occurred under his leadership, which included a number of social, economic, and political reforms. The purpose of this journal is to investigate the expansion strategies used by Umar, the achievements made during his reign, and how they impacted the progress of Islamic civilization. By using relevant data and statistics, as well as case studies from various sources, this research provides a comprehensive overview of Umar Ibn Khattab's role in Islamic history. The research results show that during the leadership of Umar bin Khattab, there was expansion in various regions and many achievements in various aspects, both in social, economic, and welfare aspects as well as other aspects. This research uses a qualitative approach by collecting data from various historical sources, including Islamic history books, academic articles, and relevant documents. The analysis was conducted by comparing various sources to gain a deeper understanding of the strategies implemented by Umar in his expansion and reforms.